Implementasi Compatibility Layer Pada Jaringan Server Diskless Berbasis Lubuntu 18.04 LTS - Farid Jatri Abiyyu; Ibnu Ziad; Ade Silvia Handayani (STEKOM PRESS, 2020)
Diskless server is a cluster computer network which uses SSH (Secure Shell) protocol to grant the client an access to the host's directory and modify it's content so that the client don't need a hardisk (Thin Client). One way to design a diskless server is by utilizing